1941
DOI: 10.1017/s0025315400014375
|View full text |Cite
|
Sign up to set email alerts
|

The Genital Ducts of Some British Stenoglossan Prosobranchs

Abstract: The foregoing pages include an account of the anatomy and histology of the male and female genital ducts of Ocenebra erinacea, Nucella lapillus, Nassarius reticulatus and Buccinum undatum. Observations have also been made on the mode of functioning of the ducts and the formation of the egg capsules.In both male and female it is possible to divide the genital ducts into a narrow and thin-walled proximal section which leads from the gonad and opens into a thick-walled glandular distal region, and in this respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
94
0
2

Year Published

1943
1943
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(113 citation statements)
references
References 9 publications
15
94
0
2
Order By: Relevance
“…Our histological study revealed that the eusperm were tightly bound to the wall of the seminal receptacle by the head (Fig. 7B-D), as observed in other prosobranchs (Fretter, 1941;Roth, 1960;Giusti and Selmi, 1985). As this implied that straight or backward swimming might have a role in penetrating into the seminal receptacle or in detaching from its wall, respectively, we dissected the seminal receptacle from a mature female, prepared a fragment of its wall and observed the movement of sperm.…”
Section: Swimming Pattern Of the Eusperm In Female Seminal Receptaclesupporting
confidence: 59%
“…Our histological study revealed that the eusperm were tightly bound to the wall of the seminal receptacle by the head (Fig. 7B-D), as observed in other prosobranchs (Fretter, 1941;Roth, 1960;Giusti and Selmi, 1985). As this implied that straight or backward swimming might have a role in penetrating into the seminal receptacle or in detaching from its wall, respectively, we dissected the seminal receptacle from a mature female, prepared a fragment of its wall and observed the movement of sperm.…”
Section: Swimming Pattern Of the Eusperm In Female Seminal Receptaclesupporting
confidence: 59%
“…The anatomyand histology of the normal female (= stage 0; ~ without any male characteristics; Figs 2c, d) and of the male genital tract (Figs 2a,b) are described by Fretter (1941) and Fretter & Graham (1962). Some information is also given by Fioroni et al (1990) and Gibbs et al (1990).…”
Section: Normal Genital System and Imposex Classificationmentioning
confidence: 98%
“…Les travaux de Dakin ( 1912), de Fretter et Graham (1962) et de Hancock (1960de Hancock ( , 1967) ont traité certains aspects de la reproduction de B. undatum en Angleterre sans toutefois aborder en détail les périodes de copulation, de ponte et de gamétogénèse. L'anatomie et le fonctionnement des différents organes de reproduction avalent cependant déjà été étudiés (Dakin, 1912;Fretter, 1941 ;Fretter et Graham, 1962).…”
Section: Résuméunclassified
“…L'analyse histologique des gonades a aussi été effectuée pour compléter les données obtenues avec les indices gonosomatiques. L'histologie des gonades est souvent utilisée dans ce genre d'étude (Pearse, 1965;Webber et Giese 1969;Fenaux, 1970;Giese et Pearse, 1974;Lambert et Dehnel 1974;Grant et Tyler, 1983a,b) et constitue une technique précise pour cerner les périodes de ponte et de gamétogénèse ( Gonor, 1972 ;Grant et Tyler, 1983a,b Johansson ( 1953,1957) et de Houston ( 1976 c'est dans les études de Fretter ( 1941de Fretter ( ,1953 Dans ce dernier compartiment ils seront conservés jusqu'au passage des ovocytes dans la glande à albumine où la fécondation a probablement lieu (Fretter, 1941 Pesage des organes. Une fois fixés, le poids total des tissus (sans coquille) a été déterminé à ± 0,01 g après avoir épongé le spécimen sur du papier buvard.…”
Section: Résuméunclassified